The Effect of Sustainability Accounting, Work Environment, and Leadership on Employee Performance - ANGGRENI, Ni Kadek Dwi Ayu; SARA, I Made; SAPUTRA, Komang Adi Kurniawan (Journal of Entrepreneurial and Business Diversity, 2023)
Purpose:This study examines and analyzes the effect of Sustainability Accounting, Work Environment, and Leadership on Employee Performance.Methodology:This research was conducted at the Office of the Central Bureau of Statistics of Bali Province with a sample of 60 respondents using a saturated sampling technique. All data obtained from the questionnaire distribution is feasible, then analyzed using multiple linear regression and hypothesis testing (t-test and f-test).Findings:The study results show that (1) Sustainability Accounting positively affects Employee Performance at the Office of the Central Bureau of Statistics of Bali Province. It shows that the better or increasing the Sustainability Accounting, the more employee performance will also increase at the Office of the Central Bureau of Statistics of the Province of Bali (2) The work environment has a positive effect on Employee Performance at the Office of the Central Bureau of Statistics of the Province of Bali. It shows that the better or increasing the work environment, the more employee performance will also increase at the Office of the Central Statistics Agency of the Province of Bali (3) Leadership has a positive effect on Employee Performance at the Office of the Central Statistics Agency of the Province of Bali.Implication:It shows that the better or increasing the leadership, the higher the performance of employees at the Office of the Central Bureau of Statistics for the Province of Bali.